Consistent determination of geometrically necessary dislocation density from simulations and experiments. (October 2018) - Das, Suchandrima; Hofmann, Felix; Tarleton, Edmund
Abstract: The use of Nye's dislocation tensor for calculating the density of geometrically necessary dislocations (GND) is widely adopted in the study of plastically deformed materials. The "curl" operation involved in finding the Nye tensor, while conceptually straightforward has been marred with inconsistencies and several different definitions are in use. For the three most common definitions, we show that their consistent application leads to the same result. To eliminate frequently encountered confusion, a summary of expressions for Nye's tensor in terms of elastic and plastic deformation gradient, and for both small and large deformations, is presented. A further question when estimating GND density concerns the optimization technique used to solve the under-determined set of equations linking Nye's tensor and GND density. A systematic comparison of the densities obtained by two widely used techniques, L 1 and L 2 minimisation, shows that both methods yield remarkably similar total GND densities. Thus the mathematically simpler, L 2, may be preferred over L 1 except when information about the distribution of densities on specific slip systems is required. To illustrate this, we compare experimentally measured lattice distortions beneath nano-indents in pure tungsten, probed using 3D-resolved synchrotron X-ray micro-diffraction, with those predicted by 3D strain-gradient crystal plasticity finite element calculations. The results are in good agreement and show that the volumetric component of the elastic strain field has a surprisingly small effect on the determined Nye tensor. This is important for experimental techniques, such as micro-beam Laue measurements and HR-EBSD, where only the deviatoric strain component is measured. Graphical abstract: Image 1 Highlights: A consistent approach to calculating Nye tensor is presented. 3D crystal plasticity and Laue diffraction measurements are directly compared. Elastic volumetric strain has negligible influence on Nye's dislocation tensor. Minimisation of energy accurately distributes GND density over slip systems. Total dislocation density from minimisation of energy and density squared match.